Gaya Kepemimpinan, Budaya Organisasi dan Motivasi terhadap prestasi santri (Studi Kasus di Pesantren Terpadu Daaruttaqwa Cibinong Bogor – Jawa Barat) - Husein, Mohammad Adam; Indupurnahayu, Indupurnahayu; Rahim, Anwar (Jurnal Manajemen, 2018)
The objectproblem of research is the style of leadership applied to the santri is still not good, the application of organizational culture is still low and the student’s motivation is still inconsistent, so it seems the performance of santri looks not improved well in recent years. This study aims to analyze the influence of leadership style, organizational culture and student’s motivation achievement in DaaruttaqwaIslamic Integrated Boarding School. Technique of data retrieval is using questionnaire given to respondent (student) as much as 203 persons. The analysis tool used is SEM (Structural Equation Modelling). The results showed that the coefficient path between leadership style and organizational culture has an effect on motivation and has an impact on student achievement in DaaruttaqwaIslamic Integrated Boarding School Cibinong Bogor.